Habitat preferences by wild boar Sus scrofa in southern Sweden based on clusters of GPS positions - Broberg, Emilia (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2008)
The wild boar is a reintroduced game species in Sweden which has become a problem species because of damage on crops and causing traffic accidents. This is a comparative study with the aim to answer the following questions: (i) which habitat sites are most frequently visited by wild boar (ii) what are the characteristic features of the most frequently used habitats, and (iii) in what way do the wild boar use these habitats? Clusters of sites frequently visited by wild boar were defined from a study in the southernmost part of Sweden, where one female (supposed to be the leader sow) in each group of 13 wild boar hoards was equipped with a GPS/GSM-collar. The GPS coordinates were managed in ArcGIS 9.1 to find the clusters. Only night clusters (between sunset and sunrise), were used, i.e. during the time animals are most active. Clusters (also called wild boar positions) were matched and compared with random positions (from the same habitat type). In the field the clusters were expected to be related to either a) food search, b) resting sites, c) farrowing nests or d) other activities in the following four defined habitat types (called terrain types below): 1) Deciduous forest, 2) Coniferous and mixed forest, 3) Open area, e.g. pasture for grazing or meadow and 4) Agricultural land (cultivated areas). In the defined study sites the following variables were measured; vegetation in the ground layer, field layer, bush layer and tree layer, direct light on the ground, humidity and shelter. One third of the observed wild boar positions shown to be feeding sites, i.e. sites with supplementary food for the wild boar provided by hunters. However, those clusters were not included in the analyses because the study focused on natural conditions. The terrain type among 1) Deciduous forest, 2) Coniferous and mixed forest, 3) Open area and 4) Agricultural land most frequently visited by wild boar showed to be Coniferous and mixed forest, which also contributed to most of the sites for supplementary feeding. Clusters defined as farrowing nests made up about one tenth of the clusters. The remaining clusters were assumed to have been used for food search or other activities. The results showed significant differences within matched pairs in habitat defined as Open area. There, the wild boar visited more areas with bushes and trees compared to random samples. Significant difference were also found between wild boar positions and random positions for mosses Bryophyta and Marchantiophyta, Wood-sorrel Oxalis acetosella and European beech Fagus sylvatica. No significant differences for the variables Direct light on the ground or Humidity appeared in this study.